Influence of Digital Adaptation on Work Engagement through the Psychological Well-Being of Employees of Private Hospitals in Bandung City - Anisya Indra Shara; Wilson Bangun (SAFE-Network, 2026)
Digital transformation in the healthcare sector requires employees to continuously adapt to rapid technological changes. In private hospitals, the implementation of digital systems such as Hospital Information Systems, electronic medical records, and patient service applications aims to improve efficiency and service quality. However, the success of digital transformation depends not only on technological readiness but also on employees’ psychological and professional adaptability. This study aims to examine the effect of digital adaptation on work engagement and to analyze the mediating role of psychological well-being among employees of five private hospitals in Bandung City. A quantitative explanatory survey design was employed. Data were collected through a five-point Likert-scale questionnaire distributed to 155 medical and non-medical employees selected using purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4.0. The findings are expected to provide empirical evidence on how digital adaptation enhances psychological well-being and work engagement. Theoretically, this study strengthens the application of the Job Demands–Resources Model in the context of hospital digitalization. Practically, the results may inform hospital management in developing human resource strategies focused on digital readiness and employee well-being.